A novel drug–drug nanohybrid for the self-delivery of porphyrin and cis-platinum. Issue 63 (12th November 2019) - Shan, Changfu; Ru, Jiaxi; Zhang, Meina; Cao, Jing; Liu, Weisheng; Guo, Huichen; Tang, Yu
Abstract : A novel self-delivery drug–drug system nanohybrid constructed by the coordination assembly of porphyrin and cis -platinum was used for synergetic photodynamic therapy and chemotherapy. Abstract : The thriving development of nanotechnology has greatly promoted the development of drug delivery systems (DDSs) in the past decades. However, most DDSs themselves cannot serve as diagnostic reagents and must be metabolized, by which they may become poisonous and even cause immune reactions. In this study, a novel self-delivery drug–drug system (SDDS) nanohybrid based on the coordination assembly of a photodynamic reagent, tetra-(4-carboxyphenyl)porphyrin (TCPP), and a chemotherapy reagent, cis -platinum, was designed and synthesized. The four carboxyl groups of TCPP can compete with the chloride ions of cis -platinum by coordination interactions, forming a TCPP- cis -platinum nanohybrid (PCNH) for the purpose of photodynamic/chemotherapeutic synergistic treatment with a combinational index of 0.28. Meanwhile, the PCNH system can effectively protect the photosensitizer TCPP from photobleaching when irradiated continuously in the photodynamic therapy (PDT) process, which is very crucial for PDT. Furthermore, introduction of the heavy atom platinum can greatly enhance the producing efficiency of 1 O2 by 46%. In addition, the red emission fluorescence of TCPP is beneficial for monitoring and tracing the process of drug delivery when used in vitro . This work may pave a new way for the design of new integrated nanohybrids for diagnosis and synergistic treatment.